Lopinavir-Ritonavir: Effects on Endothelial Cell Function in Healthy Subjects - Grubb, Jessica R.; Dejam, André; Voell, Jocelyn; Blackwelder, William C.; Sklar, Peter A.; Kovacs, Joseph A.; Cannon, Richard O.; Masur, Henry; Gladwin, Mark T. (The Journal of infectious diseases, 2006)
To differentiate between the effects that antiretroviral drugs have on the endothelium and the secondary effects that they have on immune function, viral load, and dyslipidemia, 6 non–human immunodeficiency virus–infected human subjects were treated with lopinavir-ritonavir for 1 month and, on the basis of forearm blood flow, the treatment’s effects on endothelial cell function were measured. Surprisingly, after exposure to lopinavir-ritonavir, absolute forearm blood-flow responses to the endothelium-dependent vasodilator, acetylcholine, increased significantly (P=.03), and forearm blood flow decreased to a greater extent during specific inhibition of NO synthase by NG-monomethyl-l-arginine. Thus, in this small cohort of subjects, short-term treatment with lopinavir-ritonavir does not appear to directly promote endothelial cell dysfunction